Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournaments Untuk Meningkatkan Keaktifan Belajar Siswa Kelas VIII-A SMPN 1 Keruak Pada Mata Pelajaran Pendidikan Pancasila - Nurmaizura, Dila; Sumardi, Lalu; Kurniawansyah, Edy (JPK (Jurnal Pancasila dan Kewarganegaraan), 2025)
This study aims to determine the application of the Teams Games Tournaments cooperative learning model to increase the learning activity of students in class VIII-A of SMPN 1 Keruak in Pancasila Education. The type of research used was Classroom Action Research (CAR) based on the Kemmis and Mc Taggart model. The stages of classroom action research consisted of four stages, namely 1 planning, 2 implementation, 3 observation, and 4 reflection. The research subjects were 30 students in class 8A at SMPN 1 Keruak in the 2024/2025 academic year. The data collection techniques used were observation and interviews. The research instruments were observation sheets of student learning activities and observation sheets of teacher teaching activities. The data analysis techniques used were quantitative and qualitative data analysis. The indicator of successful action was marked when student learning activity increased to the active category with the number of students reaching 75% learning activity. The results showed that there was an increase in Pancasila education learning activity among 8A students at SMPN 1 Keruak after implementing the Teams Games Tournaments cooperative learning model, both in cycle I and cycle 2. In cycle 1, the level of student learning activity was in the less active category, meaning that students were not yet able to achieve the success indicator, with a percentage of 50.